Part 13 - Expanding the bracket and simplifying III | Maths Made Easy

Surds GCSE Maths Revision

Part 13 – Expanding the bracket and simplifying III

Example:

Expand and simplify √3 (√2+2)+2√2 (√3-3)

Worked Solution:

Using BIDMAS (for more information please refer to “Order of Operation” tutorial), and the formulae m√a×n√b≡=(m×n) √(a×b)≡(mn) √ab and m√a±n√a≡(m±n) √a:

Expand the brackets

√3 (√2+2)+2√2 (√3-3)=√3×√2+2√3+2√2×√3-3×2√2

Multiply through to simplify

 √3×√2+2√3+2√2×√3-3×2√2=√6+2√3+2√6-6√2

 Simplify:

√6+2√3+2√6-6√2=(1+2) √6+2√3-6√2=2√3+3√(6 )-6√2


Your turn:

Expand and simplify √5 (2√7-1)- √7 (3-3√5)

Your answer can be written in the form: -√a-3√b-√35

Find the value of a and b.

Enter your answer here:
a=
b =

Need some extra help? Find a tutor now

Or, call 020 3633 5145